Peter C. Petersen letter to Nicholas S. Halmi regarding fall migration, 1976 - Petersen, Peter C.et al (1976)
Fall migration report contributed by Peter C. Petersen in a letter to Nicholas S. Halmi, August 23, 1976. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1976. Epson - sheet feed/flatbed